Oncogene Mutations in Cancer and Dysplasia Associated with Inflammatory Bowel Disease - J Chen; C-M Chai; W Dalu; L Shen; F Fromowitz; C Compton; MV Viola (Canadian Journal of Gastroenterology)
Chronic inflammatory bowel disease (IBO) predisposes affected individuals to the development of invasive colon cancer. Increased cancer risk has been seen in ulcerative colitis and Crohn's disease in Western societies as well as in schistosomal colitis in China. In this study it was found that the frequency of the 12th codon of c-Ki-ras, as well as the specific amino acid substitutions, were similar in sporadic colon cancers, cancers associated with ulcerative colitis in the United States, and colon cancers found in patients with schistosomal colitis in Jiangsu province in China. Further, activating mutations of codon 12 of e-Ki-ras were found in high grade dysplastic lesions in chronic ulcerative colitis. The latter finding indicates that some dysplasias are clonal proliferative lesions with genetic characteristics associated with invasive cancer.